2022
DOI: 10.1108/bij-03-2022-0161
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the relationships between the barriers to implementing machine learning for accident analysis: the Indian petroleum industry

Abstract: PurposeThis paper aims to identify, prioritise and explore the relationships between the various barriers that are hindering the machine learning (ML) adaptation for analysing accident data information in the Indian petroleum industry.Design/methodology/approachThe preferred reporting items for systematic reviews and meta-analysis (PRISMA) is initially used to identify key barriers as reported in extant literature. The decision-making trial and evaluation laboratory (DEMATEL) technique is then used to discover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…SWARA, COPRAS, FANP, FAHP, FTOPSIS, SAW, and EDAS [31] The study investigates barriers to ML implementation for accident analysis in the Indian oil industry, aiming to identify and analyze these barriers to improve safety measures.…”
Section: Author Application Of Problemmentioning
confidence: 99%
“…SWARA, COPRAS, FANP, FAHP, FTOPSIS, SAW, and EDAS [31] The study investigates barriers to ML implementation for accident analysis in the Indian oil industry, aiming to identify and analyze these barriers to improve safety measures.…”
Section: Author Application Of Problemmentioning
confidence: 99%
“…AI provides many transformational benefits to organisations across all industries and sectors (Alshahrani et al, 2021;Dennehy et al, 2022;Dwivedi et al, 2021;Elbanna et al, 2020;Vassilakopoulou et al, 2022). Recent studies have reported that AI can lead to new forms of business value (Enholm et al, 2022;Mikalef and Gupta, 2021), dynamic business-to-business relationships (Dwivedi and Wang, 2022;Keegan et al, 2022), enriched customer experiences (Jain et al, 2022;Griva et al, 2021;Kautish and Khare, 2022), enhanced human capabilities (Dwivedi et al, 2021), resilient supply chains (Zamani et al, 2022) and improved safety in the workplace (Gangadhari et al, 2022).…”
Section: Introductionmentioning
confidence: 99%